Kinetic theory of information—the dynamics of information - Treumann, Rudolf A.; Baumjohann, Wolfgang (Frontiers in Physics, 2015)
A kinetic approach to the notion of information is proposed, based on Liouville kinetic theory. The general kinetic equation for the evolution of the N-particle information I_N in a Hamiltonian system of large particle number N1 is obtained. It is shown that the the N-particle information is strictly conserved. Defining reduced particle number information densities in phase space should be possible to obtain a kinetic equation for the ordinary one-particle information I_1I following the Bogoliubov prescription. The kinetic equation for I is a kind of generalized Boltzmann equation with interaction term depending on the hierarchy of reduced informations. This term in its general form is the most general expression for the Kolmogorov entropy rate of evolution of the information.